Perfluorocarbons: A perspective of theranostic applications and challenges - Kakaei, Nasrin; Amirian, Roshanak; Azadi, Mehdi; Mohammadi, Ghobad; Izadi, Zhila (Frontiers in Bioengineering and Biotechnology, 2023)
Perfluorocarbon (PFC) are biocompatible compounds, chemically and biologically inert, and lacks toxicity as oxygen carriers. PFCs nanoemulsions and nanoparticles (NPs) are highly used in diagnostic imaging and enable novel imaging technology in clinical imaging modalities to notice and image pathological and physiological alterations. Therapeutics with PFCs such as the innovative approach to preventing thrombus formation, PFC nanodroplets utilized in ultrasonic medication delivery in arthritis, or PFC-based NPs such as Perfluortributylamine (PFTBA), Pentafluorophenyl (PFP), Perfluorohexan (PFH), Perfluorooctyl bromide (PFOB), and others, recently become renowned for oxygenating tumors and enhancing the effects of anticancer treatments as oxygen carriers for tumor hypoxia. In this review, we will discuss the recent advancements that have been made in PFC’s applications in theranostic (therapeutics and diagnostics) as well as assess the benefits and drawbacks of these applications.